Android Apps for Education: An International Collaboration - Brent Gonzales, Phuttaporn Sanchindapong, Pichaya Prompraphai and Supasit Tengkew, Kirk Scott, Supanee Sengsri, Ringo Tyson (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 1 (2558): January - April 2015DO - 10.14456/jcdr.v8i1.924, 2015)
This paper describes the participants, activities, and outcomes of a project which introduced educational Android apps and the software for making them to students and teachers in schools in the United States and Thailand. The basis for the project is the Android application architecture, which separates code (app logic) from resources (textual or media content). This makes it possible to design app templates for learning tools such as flash cards, as well as separate software which allows non-programmers to gather and assemble materials to populate the app templates. The project included templates for flash cards, sequences of multiple choice questions, and apps in which each screen displayed the steps of a problem description, algorithm, or solution in sequential order. The project demonstrated that the software was straightforward to use. The approach was suitable both for school students to gain experience organizing information and for teachers to translate source materials tailored to their needs into high quality apps appropriate for use in the classroom. The project also demonstrated that with modest technical support, the contents could easily be integrated into apps which were then distributed over the Internet.   Keywords: App Template, Android Apps for School
Keywords: App Template, Android Apps for School